African Handbook of Climate Change Adaptation 2021
DOI: 10.1007/978-3-030-45106-6_57
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Capacity to Mitigate Climate Variability and Food Insecurity of Rural Communities Along River Tana Basin, Kenya

Abstract: Climate variability is one of the leading natural threats and a root cause of food insecurity in the developing world, more so in Africa. It is a major impediment to the accomplishment of the global Sustainable Development Goals (SDGs), Vision 2030 and Big Four agenda in the Kenyan context. The rise in occurrence and brutality of extreme events resulting from variability of climate including prolonged flooding and drought has become more pronounced in the relatively drier areas. This chapter presents a synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This difference between adaptive capacity and resistance capacity is very important when considering food security at household through to global levels and is worthy of further research. Whilst adaptive capacity is considered within the literature in terms of food security, for example, in Kenya [ 116 , 117 ] and Ethiopia [ 118 ], among others, resistance capacity has not been widely studied. The work of Folke et al [ 119 ] suggested that food security resilience needs to be considered in terms of adaptive capacity, resistance capacity, i.e., surviving shocks whilst retaining existing structures and functionality, and transformative capacity to transition to new models of operation.…”
Section: Discussionmentioning
confidence: 99%
“…This difference between adaptive capacity and resistance capacity is very important when considering food security at household through to global levels and is worthy of further research. Whilst adaptive capacity is considered within the literature in terms of food security, for example, in Kenya [ 116 , 117 ] and Ethiopia [ 118 ], among others, resistance capacity has not been widely studied. The work of Folke et al [ 119 ] suggested that food security resilience needs to be considered in terms of adaptive capacity, resistance capacity, i.e., surviving shocks whilst retaining existing structures and functionality, and transformative capacity to transition to new models of operation.…”
Section: Discussionmentioning
confidence: 99%
“…Without human insights, data and the hard sciences will not be able to address the challenges of the future since adaptation is an inherently human endeavor (Shah, 2020). In addition, adaptation is determined by socioeconomic context and location (Bhatta et al, 2015) and as such, small-scale farmers' understanding of climate change is necessary for effective adaptation strategies (Karienye and Macharia, 2021). Without understanding, coping strategies and social safety nets are put under increased strain (Thornton et al, 2014).…”
Section: Literature Review the Theoretical Background Of Adaptation ...mentioning
confidence: 99%
“…The impact of inadequate and poor water quality is mainly hard felt in the arid and semi-arid areas, which are on the rise due to deforestation, land degradation and the impact of climate change [6]. More often, these areas face torrential rains, massive flooding, sand mining and harvesting, leading to poor quality water, while other times prolonged droughts cause inadequate water supply [7][8][9].…”
Section: Introductionmentioning
confidence: 99%